Developmental validation of QIAGEN Investigator® 24plex QS Kit and Investigator® 24plex GO! Kit: Two 6-dye multiplex assays for the extended CODIS core loci. (July 2017) - Kraemer, Melanie; Prochnow, Anke; Bussmann, Michael; Scherer, Mario; Peist, Ralf; Steffen, Carolyn
Highlights: Investigator 24plex QS Kit was developmentally validated for use extracted DNA, e.g. from casework samples. Investigator 24plex GO! Kit was developmentally validated for direct amplification of reference samples. Quality Sensor was shown to predict inhibition and to distinguish inhibited from degraded samples. Abstract: The original CODIS database based on 13 core STR loci has been overwhelmingly successful for matching suspects with evidence. In order to increase the power of discrimination, reduce the possibility of adventitious matches, and expand global data sharing, the CODIS Core Loci Working Group determined the expansion of the CODIS core loci to 20 STR plus three additional "highly recommended" loci (SE33, DY391, Amelogenin) Hares, 2015, 2012[1, 2] . The QIAGEN Investigator 24plex QS and Investigator 24plex GO! Kits are 6-dye multiplex assays that contain all markers of the expanded 23 CODIS core loci along with a unique internal performance control that is co-amplified with the STR markers. The "Quality Sensor" generates additional information for quality control and performance checks. Investigator 24plex QS is designed for purified DNA from casework and reference samples, whereas 24plex GO! is dedicated to direct amplification of reference samples, like blood or buccal cells on FTA or swabs. A developmental validation study was performed on both assays. Here, we report the results of this study which followed the recommendations of the European Network of Forensic Science Institutes (ENFSI)[3] and the Revised Validation Guidelines of the Scientific Working Group on DNA Analysis Methods (SWGDAM)[4] . Data included are for PCR-based procedures e.g. reaction conditions, effects of PCR annealing temperature variations, amplification cycles or cyclers, sensitivity (also in the context of the Quality Sensor), performance with simulated inhibition, stability and efficiency, precision, reproducibility, mixture study, concordance, stutter, species specificity, and case-type samples. The validation results demonstrate that the Investigator 24plex QS and Investigator 24plex GO! Kits are robust and reliable identification assays as required for forensic DNA typing in forensic casework analysis and databasing.